Synthesis of ophiocerins A, B and C, botryolide E, decarestrictine O, stagonolide C and 9-epi-stagonolide C employing chiral hexane-1,2,3,5-tetraol derivatives as building blocks - Show, Krishanu; Kumar, Pradeep (European Journal of Organic Chemistry, 2016)
An organocatalytic approach to the synthesis of (2R,3S)-hexane-1,2,3,5-tetraol (11) derivatives (in the forms of different stereoisomers and bearing different protecting groups) has been developed. The key chiral intermediates 11 were prepared with complete stereocontrol through the proline-catalyzed intermolecular aldol reaction between acetone and d-glyceraldehyde acetonide. The synthetic utility of the intermediates was demonstrated by their transformation into the title hydroxylated pyrans and a variety of unsaturated lactones through standard synthetic protocols.